EFEKTIVITAS SISTEM PELEPASAN INFORMASI MEDIS PENGGUNA ASURANSI SWASTA DENGAN TAMPILAN MOBILE PADA RUMAH SAKIT DAERAH MANGUSADA KABUPATEN BADUNG - Ayu Putu Sriantary (ITKM WIDYA CIPTA HUSADA, 2022)
The Mangusada Regional Hospital (RSD) provides medical information release services for private insurance purposes. The retrieval and recording of the medical information release reports are still carried out manually, the applicant comes directly to the hospital. The time for taking the release of medical information in accordance with standard operating procedures (SOPs) is 2 to 7 days. The purpose of this study was to determine the effectiveness of the medical information release system for private insurance users with a mobile display at the time of retrieval of medical information for insurance purposes. This research is quantitative research using a pre-experimental design with the type of one-group pretest-posttest design. The system development stage analysis method uses the system development life cycle (SDLC). The results of the study using the usability test obtained a percentage value of 79.58% which can be categorized as